Tomatoes, Urban and Rural Market, Price Analysis, Oyo State (2011)
"Prices are the most readily available and often the most reliable information on developing country marketing systems. The study examined the level of market integration in tomato markets in rural and urban markets of Oyo State, Nigeria. Secondary data on tomato price spanning 2003 -2010 were sourced from Oyo State Agricultural Development Programme (OYSADEP). The data were analyzed using Augmented Dicker Fuller (ADF) test. Indices of market concentration were also used to measure the degree of market integration. Results indicated that the maximum rural price of tomato was N131.74/kg in May, 2009 while the minimum price was N43.23/kg in August, 2004. In the urban areas, the maximum price was N132.I3/kg in May, 2009 while the minimum price was N40.98tkg in September, 2004. The restilts also revealed that prices of tomato were stationary at their level. Urban tomato market does not granger cause rural tomato market (P > 0.05), while rural tomato market granger cause urban tomato market (P< 0.05). None of the markets links exhibited bi -directional granger causality or simultaneous feedback relationship. The Index of market connection (IMC) indicates that the markets exhibit low short run market integration. It is recommended that there should be efficient flow of information, good access road and infrastructural development to improve market performance."